2022
DOI: 10.1007/s10566-022-09680-2
|View full text |Cite
|
Sign up to set email alerts
|

High Rates of Anxiety Among Adolescents in a Partial Hospitalization Program

Abstract: Background Anxiety disorders are garnering increasing attention for their contribution to high-risk issues and functional impairment. Adolescents are typically admitted to partial hospitalization programs (PHPs) due to high-risk presentations. However, the frequency of anxiety disorders in PHPs is not well-established, in part because anxiety can be overlooked in acute settings due to limited lengths of stay and focus on stabilization. Objective This study aims to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 59 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Although the PHP does not have programming to address eating disorders or substance abuse/dependence as primary diagnoses, it is able to support adolescents who are concurrently struggling with substance abuse or disordered eating. A medical record review of 158 patients enrolled in this PHP, Pelcovitz et al (in press) found that the mean age was 15.49 years old, the majority of patients (64.1%) were female and non-Hispanic (75.7%). In this sample, 60.6% of patients were Caucasian and 12.0% self-identified as belonging to more than one race.…”
Section: Preimplementation Contextmentioning
confidence: 99%
“…Although the PHP does not have programming to address eating disorders or substance abuse/dependence as primary diagnoses, it is able to support adolescents who are concurrently struggling with substance abuse or disordered eating. A medical record review of 158 patients enrolled in this PHP, Pelcovitz et al (in press) found that the mean age was 15.49 years old, the majority of patients (64.1%) were female and non-Hispanic (75.7%). In this sample, 60.6% of patients were Caucasian and 12.0% self-identified as belonging to more than one race.…”
Section: Preimplementation Contextmentioning
confidence: 99%
“…According to research, 63% of children who were hospitalized reported pain, and 29% of those children had pain before they were admitted (Cardona et al, 2019). Most people (82%) who are hospitalized experience extreme anxiety (Bajpai et al, 2017), and 75% are determined to have anxiety disorder (Pelcovitz et al, 2023). The primary driver of this high nervousness is insufficient atraumatic care because of the absence of parental inclusion or support.…”
Section: Introductionmentioning
confidence: 99%